Changes to balance dynamics following a high-intensity run are associated with future injury occurrence in recreational runners - Aquino, Mariana R. C.; Liddy, Joshua J.; Napoli, C. Dane; Fonseca, Sérgio T.; van Emmerik, Richard E. A.; Busa, Michael A. (Frontiers in Network Physiology, 2023)
Background: Fatigue is associated with increased injury risk along with changes in balance control and task performance. Musculoskeletal injury rates in runners are high and often result from an inability to adapt to the demand of exercises and a breakdown in the interaction among different biological systems. This study aimed to investigate whether changes in balance dynamics during a single-leg squat task following a high-intensity run can distinguish groups of recreational runners who did and did not sustain a running-related injury within six months. Methods: Thirty-one healthy recreational runners completed 60-second of single-leg squats before and after a high-intensity run. Six months after the assessment, this cohort was separated into two groups of 13 matched individuals with one group reporting injury within this period and the other not. Task performance was assessed by the number of repetitions, cycle time, amplitude, and speed. To evaluate balance dynamics, the regularity and temporal correlation structure of the center of mass (CoM) displacements in the transverse plane was analyzed. A two-way ANOVA calculated the interaction between groups (injury, non-injured) and time (pre, post-test). Additionally, a one-way ANOVA investigated the percent change difference of each group across time. Results: The injured group presented more regular (reduced entropy; 15.6%) and diffusive (increased short-term correlations; 5.6%) CoM displacements after a high-intensity run. No changes were observed in the non-injured group. The within-subject percent change was more sensitive in demonstrating the effects of fatigue and distinguishing the groups, compared to group measured values. No differences were observed in task performance. Discussion: Individuals who are more likely to get injured in the future present decrements in balance dynamics when exposed to fatigue. The single-leg squat test adopted appears to be a potential screening protocol that provides valuable information about balance dynamics for identifying a diminished ability to respond to training and exercise.